Kids' Microwave Step-by-Step Recipes - Fergus, Mary Pat; Illustrated by Fergus, Mary Pat and Hunter, Jayne (Sydney Murdoch Books, 2002)
This cookbook is designed for children cooking with a microwave. Each of the over 100 recipes features colour photographs. Each recipe is rated for ease of preparation, for ease of use and understanding. There is also an indication of how long a dish will take to prepare.
Include Color Illustrations and Index
Keywords: Microwave cooking